COST OF GOODS ANALYSIS WITH THE FULL COSTING METHOD - Siti Sarah (Nomico, 2024)
This study aims to analyze the determination of cost of goods using the full costing method. This method takes into account all production costs, both direct and indirect costs, to determine the cost of the product. This research will discuss the basic concept of the full costing method, its implementation in the business environment, and its advantages and disadvantages. The research methods used are literature study and data analysis. The data will be analyzed using a qualitative approach to provide a comprehensive understanding of the full costing method and its impact on the determination of the cost of product. The results of this study are expected to contribute to the understanding of the importance of the full costing method in determining accurate and relevant cost costs in the context of modern business. In addition, this research is also expected to be able to provide recommendations for business practitioners in implementing the full costing method effectively and efficiently